Merawat Kebhinekaan Menjaga Keindonesiaan: Belajar Keberagaman dan Kebersatuan dari Masyarakat Pulau - Endang Susilowati; Noor Naelil Masruroh (Department of History, Faculty of Humanities, Diponegoro University, 2018)
In the midst of the disintegration threat facing the Indonesian nation, efforts are needed to continuously maintain diversity. For that, there is nothing wrong if we look at the life of people on the island that can care for and maintain diversity. The Differences in race, ethnicity, religion, and culture do not lead to divisiveness but instead strengthen social harmony. Using this historical approach, this article intends to analyze efforts to nurture diversity undertaken by nationals domiciled on the island, taking cases in two islands, the Natuna Islands, and the Karimunjawa Islands. Sociologically and culturally Indonesian society is indeed a plural society that has great potential for the emergence of conflict and division, if not based on multiculturalism. The people of Natuna and Karimunjawa who have diversity in ethnicity, religion, and culture are still able to maintain diversity and maintain Indonesianness, so that it can be an example for other citizens, especially those near the center of government with various facilities but less able to maintain and maintain diversity.